Evaluation of Origanum vulgare Essential Oil and Its Active Ingredients as Potential Drugs for the Treatment of Toxoplasmosis - Yao, Na; Xu, Qiong; He, Jia-Kang; Pan, Ming; Hou, Zhao-Feng; Liu, Dan-Dan; Tao, Jian-Ping; Huang, Si-Yang (Frontiers in Cellular and Infection Microbiology, 2021)
Toxoplasma gondii is a serious hazard to public health and animal husbandry. Due to the current dilemma of treatment of toxoplasmosis, it is urgent to find new anti-T. gondii drugs to treat toxoplasmosis. In this study, the anti-T. gondii activity of Origanum vulgare essential oil (Ov EO) was firstly studied, and then, carvanol (Ca), the main ingredient of Ov EO was evaluated using the MTT assay on human foreskin fibroblast (HFF) cells in vitro. The cytotoxicity was evaluated using the MTT assay on HFF cells. The CC50 of Ov EO and Ca was 134.9 and 43.93 μg/ml, respectively. Both of them exhibited anti-parasitic activity, and inhibited the growth of T. gondii in a dose-dependent manner. For the inhibition effect, Ca was better than Ov EO at the same concentration, the IC50 of Ov EO and Ca was 16.08 and 7.688 μg/ml, respectively. In addition, treatment with Ca, was found to change the morphology of T. gondii tachyzoites and made their shapes curl up. These results showed that Ca was able to inhibit the proliferation of T. gondii by reducing invasion, which may be due to its detrimental effect on the mobility of tachyzoites. Our results indicated that Ca could be a potential new and effective drug for treating toxoplasmosis.